Faktor-Faktor Yang Mempengaruhi Efektivitas Penyaluran BLT Desa Mengwi, Kabupaten Badung - I Nyoman Gede Marta; Ni Rai Artini; I Gusti Ayu Meta Purmina; Ngurah Made Novianha Pynatih (RELASI : JURNAL EKONOMI, 2023)
This paper will analyze the factors that influence the effectiveness of direct cash assistance. The instruments in this analysis include effectiveness, implementation, community satisfaction and quality of service in the distribution of Village Fund Direct Cash Assistance in Mengwi Village, Mengwi District, Badung Regency. The type of data in this study is primary data, which means that the data is collected according to the interests of the current research. In this study, the structural equation analysis used was the Structural Equation Model (SEM) with an alternative Partial Least Square PLS (component based SEM). Statistical analysis shows that implementation has a positive and significant effect on service quality. Community satisfaction has a positive and significant effect on service quality. implementation has a positive and significant effect on effectiveness. Community satisfaction has a positive and significant effect on effectiveness. Service quality has a positive and significant effect on the effectiveness of the distribution of the BLT (Direct Cash Assistance) program in Mengwi Village, Mengwi District, Badung Regency. Test the path analysis between variables that mediate variable service quality on the effect of implementation on effectiveness. The next path coefficient, that the mediating variable of service quality on the effect of community satisfaction on the effectiveness of the distribution of the Direct Cash Assistance program in Mengwi Village, Mengwi District, Badung Regency.